Pengaruh Persepsi Tarif Pajak Terhadap Kepatuhan Wajib Pajak UMKM (GEMA EKONOMI, 2023)
The success of national development is influenced by various factors including taxes as a source of state revenue, but the level of tax compliance in Indonesia is still low even though micro, small and medium enterprises continue to increase every year. This research aims to determine the perception of tax rates on MSME taxpayer compliance. This research uses quantitative research methods, while data collection techniques are carried out using questionnaires and literature studies. The population in this research is MSMEs in Indonesia, while the sample used in this research is 100 samples using random sampling technique. The research results show that the perception of tax rates has a positive and significant effect on MSME taxpayer compliance. This is because individual perceptions of tax rates focus on the fairness of the tax burden that society bears, so that if individuals have a perception that is commensurate and or appropriate to the tax rate charged, it will encourage individuals to complete their tax obligations